Evaluation of The Implementation Village Head's Policy in The Management of Financial Administration in Mekar Sari Village - Hadi, Sofyan; Ermaini, Ermaini; Mustika, Mustika (PT. BERBAGI TEKNOLOGI SEMESTA, 2025)
This study aims to evaluate the implementation of village head policies in managing the financial administration of Mekar Sari Village. The main focus is on the extent to which the principles of transparency, accountability, and participatory governance are applied throughout all stages, from planning to financial reporting. This research adopts a descriptive qualitative approach by collecting data through in-depth interviews, field observations, and documentation. The findings reveal weaknesses in the application of good financial governance principles. Limited community involvement in village deliberations, inadequate financial documentation, and the low capacity of village officials are the main obstacles. These results suggest the need to strengthen the competencies of village apparatus and enhance community-based monitoring systems to achieve more transparent and accountable financial administration.